Growth and volatility of tax revenues in Latin America - Hans Fricke; Bernd Süssmuth (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2013)
Against the backdrop of high macroeconomic instability and the need to meet the demands of public spending, we analyze the trade-off between growth and volatility of tax revenues in Latin America. Short-run and long-run elasticities for a sample of eleven economies are estimated accounting for state-dependent asymmetric reactions. Controlling for composition of revenue sources and other idiosyncrasies, we find revenues above (below) its long-run equilibrium to react stronger (weaker) to business cycle dynamics. Our detailed elasticity estimates can give some orientation on how to stably reach higher tax levels on the way to develop an adequate internal tax system.
Keywords: 330